Nutrition Counseling For Pregnant Women As An Effort To Prevent Stunting In Simasom Village, Padangsidimpuan Angkola Julu District, 2025 - Putri, Yolanda; Harahap, Meilani; Hasibuan, Darma Afni; Siregar, Rahmi Wahida; Siregar, Nurmasinar; Hafni, Seri (PT Inovasi Pratama Internasional, 2025)
Stunting remains a serious public health problem in Indonesia, especially in rural areas. Simasom Village, Padangsidimpuan Angkola Julu District, is an area vulnerable to stunting due to limited knowledge about maternal nutrition during pregnancy, economic constraints, and strong local myths that restrict nutritious food intake. This community service activity employed a health promotion approach through direct nutrition counseling for pregnant women at an integrated health post (Posyandu). The method included pre-test and post-test assessments using questionnaires to measure knowledge levels, direct counseling using leaflets, and anthropometric measurements (weight, height, Mid-Upper Arm Circumference). The activity involved nine pregnant women. The activity showed a significant increase in participants' knowledge. Pre-test results indicated 68.8% of pregnant women had poor knowledge about nutrition and stunting prevention. After the counseling, the post-test results showed a decrease to only 12.5% with poor knowledge, while 87.5% achieved a good knowledge level, indicating a 56.3% improvement. Anthropometric data revealed that most participants had normal nutritional status, although two pregnant women required further nutritional intervention based on their Mid-Upper Arm Circumference measurements. Direct nutrition counseling using leaflets is effective in significantly increasing the knowledge of pregnant women about balanced nutrition and stunting prevention. Continuous and routine educational activities at Posyandu are essential to maintain and improve maternal understanding, which is expected to lead to positive behavioral changes and contribute to stunting reduction efforts in Simasom Village.